Studi STUDI ANALISIS PERUBAHAN TUTUPAN LAHAN DI KABUPATEN SLEMAN TAHUN 2017 - 2021 DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Sugeng Wahyudiono Sugeng; Tatik Suhartati; M. Randi Mulia (Jurusan Kehutanan -FHIL-UHO, 2024)
Sleman Regency is one of the busiest cities in Indonesia. It is an urban area where various aspects and areas of human life take place such as economy, trade, housing, education, and more. Due to these activities, there have been changes in land cover that need to be managed. To understand the extent of these changes, it is utilizing GIS (Geographic Information System) is crucial. This study's goal is to ascertain the land cover condition in Sleman Regency from 2017 to 2021 and to find out the extent of land cover changes. The results showed that the area of buildings increased by 43,64 ha and settlements increased by 264,54 ha. There were reductions in protected forests by 1,04 ha, plantations by 14,54 ha, irrigated rice fields by 279,20 ha, rainfed rice fields by 2,55 ha, shrubs by 2,83 ha, and Tegalan/fields by 8,17 ha. However, airports, lakes/reservoirs, grass/vacant land, and rivers remained unchanged or experienced no decrease or increase in land cove.